Contamination of stored crop grains with Aspergillus niger fungi and production of the toxin Ochratoxin A and its negative impact when used as a feed for fish in Iraq - Hussein Kamel Ghafouri; Yasir Naser Alhamiri (Journal of Kerbala for Agricultural Sciences, 2024)
The study investigated the contamination of stored crop grains used as fish feed in Iraq by fungi capable of producing Ochratoxin A (OTA) and assessed its impact on fish farming and health. A survey revealed that all tested grain samples were contaminated with various fungi, with Aspergillus niger being the most prevalent. Among 1,400 isolates of A. niger, nine were confirmed to produce OTA at varying levels. The highest OTA concentration (80.90 µg/kg) was recorded for isolate ANK1, while the lowest (35.9 µg/kg) was found in isolate ANA1. Molecular and morphological diagnoses of the toxin-producing isolates were consistent, and their genomic sequences were archived in the NCBI database under accession codes OR452868.1 and OR449322.1. Chromatographic analysis detected OTA contamination in five out of nine samples, with the highest contamination level (6.90 µg/kg) found in sample K1F. Contamination impacted fish growth and health, increasing mortality rates to 10.8% compared to 3.5% in the control. Weight loss percentages ranged from 13.7% to 27.2% over 60 to 180 days. Blood analysis showed decreased WBC, RBC, HGB, MCHC, and PLT levels, while HCT levels significantly increased. The findings underscore the risks posed by OTA contamination to fish farming and emphasize the need for improved feed safety measures.